ADVANCES IN SOLID PHASE EXTRACTION - Mohd. Marsin Sanagi, editor; Aemi Syazwani Abdul Keyon, 1987-, editor; Wan Aini Wan Ibrahim, contributor; Mohd. Marsin Sanagi, contributor; Sazlinda Kamaruzaman, 1989-, contributor; Norfazilah Muhamad, 1987-, contributor; Chong, Mun Hwa, 1985-, contributor; Nur Atiqah Abu Bakar, 1991-, contributor; Aemi Syazwani Abdul Keyon, 1987-, contributor; Noorfatimah Yahaya, 1988-, contributor; Dyia Syaleyana Md. Shukri, 1989-, contributor; Nurul Nabilah Zainal Abidin, 1990-, contributor; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2016)
Includes bibliographical references and index :p.77